Analysis of the Effect of Workload and Compensation on the Professionalism of Islamic Religious Education Teachers in Pasuruan Regency - Ayusta Maulana Putrasari (International Consortium of Education and Culture Research Studies, 2020)
The teacher is a professional educator who has the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education through basic education, and secondary education. Workload and compensation received by the teacher can affect the teacher's professionalism. This study aims to determine the effect of workload and compensation on the professionalism of Islamic Religious Education teachers in Pasuruan Regency. The study was conducted on 50 PAI teachers in Pasuruan Regency. The analysis used in this study is multiple linear regression. Significance values ​​for workload variables (X1) and compensation (X2) were 0.023 and 0,000 (p <0.05), respectively. So it can be concluded that the workload variable (X1) has a significant effect on teacher professionalism (Y) and the compensation variable (X2) has a significant effect on teacher professionalism (Y). The coefficient value on the workload variable is known to be 0.177 which means there is a positive influence between workload on teacher professionalism. The same thing happened to the compensation variable where the coefficient value obtained was 0.253 so that the compensation variable had a positive effect on the professionalism of PAI teachers in Pasuruan Regency. The magnitude of the influence of these two variables amounted to 57.6%. The correlation coefficient value is 0.687, meaning that the independent variable and the independent variable have sufficient and positive correlation. If the independent variable increases, the dependent variable will also increase.